ENHANCING LITERARY COMPETENCE THROUGH ACTIVITY BASED LITERATURE LEARNING - Neranjani, E. Sulochana (My University, 2011)
The aim of this study is to find out how literary competencies of students who learn English Literature in Sri Lanka can be enhanced using activity based methods in the classroom. This chapter focuses on the background and the rationale for the study, definition of terms, research questions, objectives and the outline of the study.